The agrienvironmental programme in Slovakia, in 2004-2006 - M. Brodová (Agricultural Economics (AGRICECON), 2009)
Main objective of the agrienvironmental measures is to support the environmentally acceptable farming methods, the application of soil protection methods, as well as the protection and maintaining of biodiversity in agricultural landscape. The project measure Agrienvironment and animal welfare conditions in the 2004-2006 programming period was the one that attracted the highest number of applications. The total area of land farmed in compliance with the requirements under the agrienvironmental measure represented about one fifth of the total area of agricultural land in Slovakia by the end of 2006. The largest portion of the area has been farmed by legal persons. The article presents the evaluation of the selected data in a questionnaire survey among businesses involved in the agrienvironmental programme, mostly related to the structure of land fund, employment, motivation, production and diversity of farm coverage.